Explore Westonci.ca, the top Q&A platform where your questions are answered by professionals and enthusiasts alike. Join our Q&A platform to connect with experts dedicated to providing precise answers to your questions in different areas. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
To find the equation of the line passing through the intersection of [tex]\(3x + y = 7\)[/tex] and [tex]\(3y = 4x - 5\)[/tex], and parallel to [tex]\(2x - y = 3\)[/tex], follow these steps:
1. Find the intersection point of [tex]\(3x + y = 7\)[/tex] and [tex]\(3y = 4x - 5\)[/tex]:
- From the equation [tex]\(3x + y = 7\)[/tex]:
[tex]\[ y = 7 - 3x \][/tex]
- Substitute [tex]\(y = 7 - 3x\)[/tex] into the equation [tex]\(3y = 4x - 5\)[/tex]:
[tex]\[ 3(7 - 3x) = 4x - 5 \][/tex]
[tex]\[ 21 - 9x = 4x - 5 \][/tex]
[tex]\[ 21 + 5 = 4x + 9x \][/tex]
[tex]\[ 26 = 13x \][/tex]
[tex]\[ x = 2 \][/tex]
- Substitute [tex]\(x = 2\)[/tex] back into [tex]\(y = 7 - 3x\)[/tex]:
[tex]\[ y = 7 - 3(2) \][/tex]
[tex]\[ y = 1 \][/tex]
- Hence, the intersection point is [tex]\((2, 1)\)[/tex].
2. Determine the equation of the line parallel to [tex]\(2x - y = 3\)[/tex] and passing through [tex]\((2, 1)\)[/tex]:
- The general form of the equation for a line parallel to [tex]\(2x - y = 3\)[/tex] has the same slope, thus:
[tex]\[ 2x - y = C \][/tex]
- We need to find the constant [tex]\(C\)[/tex] using the point [tex]\((2, 1)\)[/tex]:
[tex]\[ 2(2) - 1 = C \][/tex]
[tex]\[ 4 - 1 = C \][/tex]
[tex]\[ C = 3 \][/tex]
- Therefore, the equation of the line is:
[tex]\[ 2x - y = 3 \][/tex]
Since this line is already in the form [tex]\(2x - y = 3\)[/tex], the required equation is:
[tex]\[ 2x - y - 3 = 0 \][/tex]
1. Find the intersection point of [tex]\(3x + y = 7\)[/tex] and [tex]\(3y = 4x - 5\)[/tex]:
- From the equation [tex]\(3x + y = 7\)[/tex]:
[tex]\[ y = 7 - 3x \][/tex]
- Substitute [tex]\(y = 7 - 3x\)[/tex] into the equation [tex]\(3y = 4x - 5\)[/tex]:
[tex]\[ 3(7 - 3x) = 4x - 5 \][/tex]
[tex]\[ 21 - 9x = 4x - 5 \][/tex]
[tex]\[ 21 + 5 = 4x + 9x \][/tex]
[tex]\[ 26 = 13x \][/tex]
[tex]\[ x = 2 \][/tex]
- Substitute [tex]\(x = 2\)[/tex] back into [tex]\(y = 7 - 3x\)[/tex]:
[tex]\[ y = 7 - 3(2) \][/tex]
[tex]\[ y = 1 \][/tex]
- Hence, the intersection point is [tex]\((2, 1)\)[/tex].
2. Determine the equation of the line parallel to [tex]\(2x - y = 3\)[/tex] and passing through [tex]\((2, 1)\)[/tex]:
- The general form of the equation for a line parallel to [tex]\(2x - y = 3\)[/tex] has the same slope, thus:
[tex]\[ 2x - y = C \][/tex]
- We need to find the constant [tex]\(C\)[/tex] using the point [tex]\((2, 1)\)[/tex]:
[tex]\[ 2(2) - 1 = C \][/tex]
[tex]\[ 4 - 1 = C \][/tex]
[tex]\[ C = 3 \][/tex]
- Therefore, the equation of the line is:
[tex]\[ 2x - y = 3 \][/tex]
Since this line is already in the form [tex]\(2x - y = 3\)[/tex], the required equation is:
[tex]\[ 2x - y - 3 = 0 \][/tex]
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.